Controlling Enzymatic Activity by Modulating the Oligomerization State via Chemical Rescue and Optical Control. (22nd October 2021) - Kropp, Cosimo; Bruckmann, Astrid; Babinger, Patrick
Abstract: Selective switching of enzymatic activity has been a longstanding goal in synthetic biology. Drastic changes in activity upon mutational manipulation of the oligomerization state of enzymes have frequently been reported in the literature, but scarcely exploited for switching. Using geranylgeranylglyceryl phosphate synthase as a model, we demonstrate that catalytic activity can be efficiently controlled by exogenous modulation of the association state. We introduced a lysine‐to‐cysteine mutation, leading to the breakdown of the active hexamer into dimers with impaired catalytic efficiency. Addition of bromoethylamine chemically rescued the enzyme by restoring hexamerization and activity. As an alternative method, we incorporated the photosensitive unnatural amino acid o ‐nitrobenzyl‐ O ‐tyrosine (ONBY) into the hexamerization interface. This again led to inactive dimers, but the hexameric state and activity could be recovered by UV‐light induced cleavage of ONBY. For both approaches, we obtained switching factors greater than 350‐fold, which compares favorably with previously reported activity changes that were caused by site‐directed mutagenesis. Abstract : Exogenous control of the association state of enzyme complexes can be used to switch activity. A cation‐π bond in the oligomerization interface was disrupted either by a Lys‐to‐Cys mutation or by incorporation of an unnatural amino acid (UAA), resulting in complex disassembly and loss of activity. For switching activity on again, Lys was chemically rescued or the UAA was decaged by light. The complex was reformed and the activity was fully restored.